Inheritance and comparison of phenotypic characters of cultivated butternut pumpkin (Cucurbita moschata (Duchesne) Poir ‘Butternut’) - Budi Setiadi Daryono; Yuanita Sekar Chintani; Hetty Nopianasanti; Dian Sartika (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.